EFEKTIVITAS PENERAPAN PIDANA DENDA DALAM PELANGGARAN LALU LINTAS: STUDI KASUS DI PENGADILAN NEGERI BOGOR - Deddi Fasmadhy Satiadharmanto; Sendi Sanjaya; Dadah Muliansyah; Syarif Hidayatullah Nasution; Zamzanie Zamzanie (Khairun Law Journal, 2025)
Traffic violations have become a significant issue in Indonesia, including in the Bogor region. Despite the implementation of fines as a penalty for traffic violations, the effectiveness of this penalty in reducing violations remains questionable. This study aims to analyze the effectiveness of fines as a penalty for traffic violations in the jurisdiction of the Bogor District Court. The research uses a case study approach, analyzing traffic violation data from 2022 to 2024 and conducting interviews with judges, police officers, and offenders. The findings reveal that while fines are effective in some cases, there are still factors such as low enforcement, inadequate public awareness, and insufficient deterrent effects that affect their success. The study also identifies the community's perception of the fine penalty system and suggests recommendations to enhance its effectiveness. The study concludes that improving the implementation of fines, along with increasing public education, could contribute to reducing traffic violations and promoting legal compliance.